APPLICATION AND LIMITATIONS OF DERIVATIVE INSTRUMENTS IN ISLAMIC FINANCE - Bakoeva Gulbakhor (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
The emergence of Islamic finance as a rapidly expanding segment of the global financial system has introduced unique perspectives on financial innovation, risk management, and ethical investment. While conventional finance relies heavily on derivative instruments such as futures, options, and swaps to hedge against financial risks, the application of these instruments within Islamic finance remains controversial due to the prohibition of riba (interest), gharar (excessive uncertainty), and maysir (speculation). This article examines the extent to which derivative instruments can be adapted to comply with Shariah principles, evaluates their practical use in Islamic financial institutions, and analyzes the ethical and legal constraints that limit their broader application. The study highlights both the potential benefits of Shariah-compliant risk management tools and the structural limitations that prevent derivatives from fully aligning with Islamic moral and jurisprudential frameworks.